ANALISIS KEUNTUNGAN DAN RISIKO PADA AGROINDUSTRI JAHE INSTAN (STUDI KASUS PADA UMKM GENDIS AYU JAHE) - Aristi, Riska; Prasmatiwi, Fembriarti Erry; Sayekti, Wuryaningsih Dwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This research aims to analyze: (1) profitability, (2) risks and mitigation actions in the instant ginger agroindustry. This study employs a case study method on the instant ginger agroindustry at UMKM Gendis Ayu Jahe, Tulang Bawang Udik District, Tulang Bawang Barat Regency. The research location was determined purposively, considering that the agroindustry is actively producing instant ginger. The respondents in this study are the owner and five employees of UMKM Gendis Ayu Jahe. Data collection was conducted from January to February 2024. The data analysis methods used in this research are profitability analysis and risk analysis using the House of Risk (HOR) method. The results show that (1) UMKM Gendis Ayu Jahe is profitable as the R/C ratio is greater than 1, and (2) the priority risk agents in UMKM Gendis Ayu Jahe are the insufficient number of raw material suppliers, fluctuations in product order quantities, scarcity of red ginger as the main raw material, the low capability of suppliers to meet red ginger needs, and sudden increases in demand volume. The priority mitigation actions at UMKM Gendis Ayu Jahe are improving relationships and communication with raw material suppliers, forming partnerships with red ginger farmers, implementing a make-to-stock production system, diversifying products using alternative raw materials, and Expanding the search area for regions that produce red ginger